2019
DOI: 10.3390/ma12091413
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Gradient Compressed Porous Metal for High-Efficiency and Thin-Thickness Acoustic Absorber

Abstract: Increasing absorption efficiency and decreasing total thickness of the acoustic absorber is favorable to promote its practical application. Four compressed porous metals with compression ratios of 0%, 30%, 60%, and 90% were prepared to assemble the four-layer gradient compressed porous metals, which aimed to develop the acoustic absorber with high-efficiency and thin thickness. Through deriving structural parameters of thickness, porosity, and static flow resistivity for the compressed porous metals, theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 31 publications
0
37
0
Order By: Relevance
“…It could be easy to confirm that reasonable range of the porosity φ was (0,1) according to its definition, as shown in Equation (18). Meanwhile, it was reported by the present literatures [1][2][3][4][8][9][10][11][12][13][14] that normal possible boundary of the static flow resistivity σ was [10000, 50000], so the investigated range in this research was set to [1000,200000], as shown in Equation (19). Moreover, the optimization target was to achieve minimized differences between the sound absorption coefficient of the experimental data α a f , d p f and that of the theoretical data α t f , d p f , as shown in Equation (20).…”
Section: Identification Of Acoustic Characteristic Parameters Of the mentioning
confidence: 68%
See 4 more Smart Citations
“…It could be easy to confirm that reasonable range of the porosity φ was (0,1) according to its definition, as shown in Equation (18). Meanwhile, it was reported by the present literatures [1][2][3][4][8][9][10][11][12][13][14] that normal possible boundary of the static flow resistivity σ was [10000, 50000], so the investigated range in this research was set to [1000,200000], as shown in Equation (19). Moreover, the optimization target was to achieve minimized differences between the sound absorption coefficient of the experimental data α a f , d p f and that of the theoretical data α t f , d p f , as shown in Equation (20).…”
Section: Identification Of Acoustic Characteristic Parameters Of the mentioning
confidence: 68%
“…The transfer matrix T mpma of the prepositive microperforated polymethyl methacrylate panel was derived according to Maa's theory [18][19][20], as shown in the Equation (8). Here, Z s was acoustic impedance, as shown in Equation (9), and its real part and imaginary part were symbolled as R and X respectively; j is the still symbol of the imaginary number, j = √ −1.…”
Section: Composite Sound Absorbing Structure and Its Theoretical Sounmentioning
confidence: 99%
See 3 more Smart Citations